Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:• The Impact of Transformational Leadership Styles on the Job Performance of Cycle Two School Teachers in Muscat Governorate, Sultanate of Oman: An Analytical StudyMs. Amal Saif Al-Humaidi• The role of governments in promoting the transition to a knowledge economy and the challenges they faceMs. Wafiah Othman Alsubhi, Ms. Maha Saleh Saad Alyahyan• The Role of Prophetic Guidance in Promoting Sustainable Peace ValuesCo-Prof. Fari’a Abdullah Ghotish Al-Khuza’i, Prof. Hanadi Eisa Mohana Ibrahim• The Level of Awareness of Kindergarten Teachers at Baghdad Al-Karkh Second Education Directorate of the Importance of Digital EducationAsst-Prof. Ola Hussein Alwan• Marital compatibility among female teachers in Hail CityMrs. Alaa Falah F. Al-Hamdhawi• Persuasive Intelligence and Its Relationship to Mindfulness Among Kindergarten TeachersLecturer\ Hind Luay Abdulhameed• The Impact of Relative Contribution of Psychological Capital and Academic Inclusion  in Predicting the Quality of Life among Female University Students in Saudi ArabiaDr. Norah Abdulrahman Almotrefi
Keywords: Journal of Educational and Psychological Sciences